1984
DOI: 10.1002/cne.902270207
|View full text |Cite
|
Sign up to set email alerts
|

A Golgi analysis of the primate globus pallidus. III. Spatial organization of the striato‐pallidal complex

Abstract: An atlas of transverse sections of the globus pallidus and striatum was established in macaque with reference to ventricular coordinates. The three-dimensional geometry of the striato-pallidal complex was investigated by means of sagittal and horizontal reconstructions. Both a personal case studied with autoradiography and data from literature were used to analyze the distribution of cortical axons into the striatum. One may distinguish two striatal territories: one, somatotopically arranged, sensorimotor terr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
1
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 212 publications
(84 citation statements)
references
References 43 publications
3
79
1
1
Order By: Relevance
“…The anatomical basis may be the triad arrangement of dopamine synapses on glutamatergic inputs to dendritic spines of striatal and cortical neurons (FIGURE 17B) (171,186) and convergence in striatum and globus pallidus (416,430). The long debated focusing effect assumes that dopamine signals suppress the effects of weaker inputs to the striatum while allowing stronger ones to pass through to the basal ganglia outputs (70,368,594).…”
Section: Immediate Dopamine Influencesmentioning
confidence: 99%
See 2 more Smart Citations
“…The anatomical basis may be the triad arrangement of dopamine synapses on glutamatergic inputs to dendritic spines of striatal and cortical neurons (FIGURE 17B) (171,186) and convergence in striatum and globus pallidus (416,430). The long debated focusing effect assumes that dopamine signals suppress the effects of weaker inputs to the striatum while allowing stronger ones to pass through to the basal ganglia outputs (70,368,594).…”
Section: Immediate Dopamine Influencesmentioning
confidence: 99%
“…For neuronal decision models involving the basal ganglia, key features are the well-organized corticostriatal projections, internal connections, and parallel loops with cortex (7,141,164,196,197,252); the synaptic convergence through the component structures (FIGURE 48B) (416,430); the separate striatal outputs with sequential inhibitory neurons (93,127); and the dopamine-mediated plasticity of corticostriatal connections (424,517,540). The basal ganglia may be involved in two distinguishable aspects of decision-making, namely, the direct selection of options and the updating of option values through reinforcement learning (57).…”
Section: Formal Neuronal Decision Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…These subdivisions are based on the nature of the cortical information that is processed in different regions of the basal ganglia. Tracing experiments in the monkey have demonstrated that the primary somatosensory, primary motor, premotor and oculomotor cortices project mainly to the putamen in the form of three somatotopic strips corresponding to the arm, face and leg (Flaherty and Graybiel, 1994;Künzle, 1975;Percheron et al, 1984). This subdivision which processes sensorimotor information is referred to as the sensorimotor territory.…”
Section: Basal Ganglia Functional Subdivisionsmentioning
confidence: 99%
“…Inputs to STN are multiple. Signals arising from the caudate and putamen are conveyed to STN via the external segment of the globus pallidus (Kim et al 1976;Kita et al 1983;Moriizumi et al 1987;Percheron et al 1984). The cerebral cortex is another source of input.…”
Section: Introductionmentioning
confidence: 99%